PENGARUH KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2016-2019) - Triyas Jumiyanti; Desy Nur Pratiwi; Sumadi Sumadi (ITB AAS INDONESIA, 2021)
This study aims to determine the significance of the effect of institutional ownership, profitability and firm size on earnings management (empirical studies on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2019). The population in this study was 61 manufacturing companies in the food and beverage sector for the period 2016 – 2019. The number of samples used in this study was 24 companies, using the purposive sampling method. There are two variables used, namely dependent and independent. The categories of independent variables are institutional ownership, profitability (ROA) and firm size. While the dependent variable category is earnings management. The analysis technique used in this research is multiple linear regression. The data is processed using SPSS 23. The partial test results show that only the profitability (ROA) variable has no significant effect on earnings management, while the institutional ownership and firm size variables have a significant effect on earnings management. Simultaneous test results show that the variables of institutional ownership, profitability (ROA) and firm size simultaneously have a significant effect on earnings management. Keywords: Earnings Management, Institutional Ownership, Profitability, Firm Size